Mathematical Thinking and Mathematical Ability and Their Development - Otojanova N.B; Sapayeva D. (Genius Journals, 2023)
In this article, mathematical thinking and mathematical character and the features of their development are revealed.
Keywords: student; mathematical thinking; mathematical ability